Laboratory report: practical biology BIO0401 - Zahari, Shafiyyah Solehah; Hamzah, Haliza; Teruk, Kamaril Azlah; Mohd Nasohah, Nor Sa'adah; Mohd Sani, Rositi Mashani (IIUM Press, International Islamic University Malaysia, 2018)
This is the Laboratory Report Practical Biology BIO0401 for Practical Biology course. Practical Biology is one of the courses offered by the Department of Biology, CFS IIUM. This laboratory report is intended for students at Foundation level to complete the report for each experiment.